Investigation of Drying Process Kinetics of Composite Granules - Zhanna Petrova (Energy Engineering and Control Systems, 2022)
Among the large number of modern environmental problems in Ukraine, waste of wastewater treatment stations occupies a special place. During biological water treatment, the separated sludge deposits are sent to the silt fields, which are the biggest problem. Today, these fields reached their capacity three times over and pose a danger, the consequences of which go far beyond environmental problems and have grown into a chain of socio-economic, technical, medical-biological and moral-ethical problems. Previously, activated sludge was used as fertilizer in the fields, but in connection with the Chornobyl Disaster, it was banned. As a result, accumulations of silt deposits were formed, which are also called obsolete. A modern solution is the compaction of sediments and the development of energy-efficient technologies for the processing of obsolete sludge and incineration in appropriate facilities. This paper presents the results of the drying process study for composite granules based on peat, sludge and biomass. The effect of coolant temperature on the drying rate shows the 1.4-fold intensification of the drying process. Theoretical studies with the construction of generalized drying curves of composite granules calculated by the method of V. V. Krasnikov showed coincidence with experimental data.